2020
DOI: 10.1002/cctc.202001160
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Synthesis of Aliphatic Acyloins Catalyzed by Thermostable Transketolase

Abstract: The thermostable transketolase from Geobacillus stearothermophilus (TK gst) was successfully engineered for the synthesis of aliphatic acyloins with varying carbon backbone lengths (C 5 À C 10) based on protein structure-guided studies. Efficient TK gst variants were identified with enhanced activities for substrate combinations of aliphatic aldehydes as acceptors together with aliphatic pyruvate homologues as donors. The TK gst single variant L382F was able to catalyze efficiently the transfer of the ketol gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 42 publications
(45 reference statements)
0
33
0
Order By: Relevance
“…Likewise, TK gst had a very similar profile activity towards these substrates and its activity towards heptanal and octanal was very low. 9 More interestingly, our results showed that TK tmar is active towards uronic acids with relative activities towards D-galacturonic acid (GalAc) and D-glucoronic acid of 52% and 53% respectively. This TK-catalysed reaction would lead to the formation of the respective 7-keto-octuronic acids.…”
Section: Substrate Scope Screeningmentioning
confidence: 66%
See 4 more Smart Citations
“…Likewise, TK gst had a very similar profile activity towards these substrates and its activity towards heptanal and octanal was very low. 9 More interestingly, our results showed that TK tmar is active towards uronic acids with relative activities towards D-galacturonic acid (GalAc) and D-glucoronic acid of 52% and 53% respectively. This TK-catalysed reaction would lead to the formation of the respective 7-keto-octuronic acids.…”
Section: Substrate Scope Screeningmentioning
confidence: 66%
“…The TK pH-based high-throughput assay proved to be effective for initial substrate scope screening for a series of aldehydes substrates using LiHPA as ketol donor. 9,38 In this work several aldehyde donors were tested including monosaccharides: C 5 (L-rhamnose, L-arabinose, D-ribose, 2-deoxy-D-ribose and Table 1 TK tmar apparent kinetic parameters towards LiHPA and glycoaldehyde (GA), were calculated following the pH-based high-throughput assay with pure TK tmar (0.25 mg mL −1 ), GA (final concentration 0.5 to 50 mM -LiHPA constant at 50 mM) or LiHPA (final concentration 5 to 100 mM -GA constant at 50 mM), phenol red (28 mM), ThDP (2.4 mM), MgCl 2 (9 mM). All reaction components were prepared in TEA 2 mM buffer pH 7 and reactions carried out 65°C.…”
Section: Substrate Scope Screeningmentioning
confidence: 99%
See 3 more Smart Citations